Epidemiology of dengue fever in Gabon: Results from a health facility-based fever surveillance in Lambaréné and its surroundings. - Jacqueline Kyungah Lim; José Francisco Fernandes; In-Kyu Yoon; Jung-Seok Lee; Regis Obiang Mba; Kang Sung Lee; Suk Namkung; Jae Seung Yang; So Hee Bae; Sl-Ki Lim; Bertrand Lell; Meral Esen; et al. (Public Library of Science (PLoS), 2021)
Background In Africa, information on dengue is limited to outbreak reports and focused on some countries with continuing transmission in West and East Africa. To estimate the proportion of dengue-positive cases among febrile patients and identify clinical indicators of dengue cases, we conducted passive facility-based fever surveillance in a catchment area population of 70,000 residents of Lambaréné and its surroundings in Gabon. Methods Non-malarial febrile patients with current fever or history of fever (≤7 days) between 1 and 55 years of age, were enrolled at Albert Schweitzer Hospital (ASH). Acute (visit 1, day of enrollment) and convalescent blood samples were collected between 10 and 21 days after enrollment. Acute/convalescent samples were tested with IgM/IgG ELISA, and a selected subset of acute samples with RT-PCR. Results Among 682 non-malarial febrile patients enrolled, 119 (17.4%) were identified as dengue-positive (94 dengue-confirmed and 25 dengue-probable cases). Of these dengue-positive cases, 14 were confirmed with PCR, and based on serotyping, two infections were identified to be DENV-2 and two were DENV-3. The majority of our enrolled patients were <25 years of age and close to 80% of our dengue-positive cases were <15 years of age. In adjusted analyses, retro-orbital pain and abdominal pain were 2.7 and 1.6 times more frequently found among dengue-positive cases, compared to non-dengue cases. Conclusion Lambaréné is not considered dengue-endemic. However, one in six non-malarial febrile episodes was found to be dengue-positive in the study period. Dengue should be considered more frequently in clinicians' diagnosis among non-malarial febrile patients in Lambaréné. Given the lack of data on dengue in Gabon, additional prospective and longitudinal studies would help to further define the burden and patterns of dengue for improved case detection.